Studi Fenomenologi: Mental Accounting Dalam Investasi Fixed Assets Pada Petani Sawit - Angkawijaya, Riky; Ikhsan, Syarbini; Rusmita , Sari (Publikasi Indonesia, 2025)
This research aims to understand how oil palm smallholders apply mental accounting in investment decisions on fixed assets, such as the purchase of heavy equipment, operational vehicles, and additional land. The approach used is qualitative with phenomenological methods to explore the subjective experience of oil palm farmers in managing and allocating financial resources. The results showed that farmers unconsciously divided funds into different